Confucian Leadership Meets Confucian Democracy. Issue 2 (August 2022) - Angle, Stephen C.
Abstract : Confucian democrats hold that the roles of Confucian political leaders must be rethought, just as the modern Confucian polity must shift from a monarchy to a constitutional democracy. This does not mean that modern Confucians must turn their backs on traditional Confucian views of leadership, however: the key traditional insights are still important, although to some degree they take on new significance in the new context of modern democratic Confucianism. Drawing on recent work by Joseph Chan and Elton Chan, I begin by outlining a traditional Confucian view of the 'inspirational' leader. Next, I unpack and then critique Jiwei Ci's argument that Confucian leadership rests on an 'identification model' of agency that is incompatible with democracy. Third, I build on some of the argument from my book Contemporary Confucian Political Philosophy: Toward Progressive Confucianism to the effect that modern Confucians need to resolve a tension within traditional Confucianism by embracing a person-based democracy instead of mass-based authoritarianism. Finally, I conclude by making explicit why Confucian democracies still need leaders playing roles that are very much in the spirit of traditional Confucian leadership.